KENDALA-KENDALA MAHASISWA PROGRAM STUDI PENDIDIKAN FISIKA FKIP UNSYIAH DALAM KULIAH SEMINAR FISIKA - Ahmad Farhan; Marwan AR; Nurmala Nurmala (Syiah Kuala University, 2015)
Seminar fisika lecture is a compulsory subject in education Prodi FKIP Unsyiah programmed in the VII Periodic half years. The fact graduat students often late to plane this, due to several constraints. The focus of discussion in this paper is to discuss whether the constraints and causes occurred the lecture program the students?. Research conducted in the physical education study program, with the subject as much as 28 graduat student that have passed through the Periodic half years VIII, but has not been programmed lecture Physics Seminar. adopt this type of qualitative descriptive with a non-parametric statistical analysts, using percentages. Concluded, largely students suffered internal constraints, among others: phisiologis, psychological, determining research problems, and lack of confidence. These constraints caused randahnya analysis capabilities, sintesis and evaluation of the concept of student. Eksteren constraints experienced by students include: lack of available funds, differences of opinion with the faculty trustee, has not been able to meet the pre-requisites Lecture, lack of available reference and academic climate and society are less supportive. This relates to the lack of scientific knowledge of the students, rarely visited the library and the scientific culture has not been properly socialized in an academic environment and a place to stay.